Exergy analysis of methane steam reformer utilizing steelmaking waste heat - Maruoka, Nobuhiro; Purwanto, Hadi; Akiyama, Tomohiro (The Iron and Steel Institute of Japan, 2010)
System analysis was conducted on a proposed combined system for methane steam reforming comprising conventional hydrogen production and waste heat recovery from steelmaking. Operating data for a conventional methane steam reforming system were collected and analyzed. The results showed that the conventional system utilized only 60% of the natural gas as raw material and the rest is consumed for supplying the reaction heat for methane steam reforming. On the basis of this data, the proposed system was evaluated on five factors—natural gas consumption, enthalpy flow, CO2 emission, cost, and exergy loss. For the proposed system, the factors were only 59.6%, 59.7%, 62.8%, 86.5%, and 65.8% of those of the conventional system, respectively. This supports the feasibility of hydrogen production from recovered waste heat. Furthermore, the proposed system is expected to contribute to the production of ‘green’ hydrogen that incurs less CO2 emission.